Thermal and electrical tuning of whispering gallery modes in liquid crystal-filled hollow glass microsphere. (10th January 2019) - Xiong, Zuoren; Zhang, Chi; Hu, Jianyang; Fu, Dongying; Lu, Yuelan; Sun, Weimin; Liu, Yongjun
Abstract: This paper demonstrates a thermally and electrically tunable hollow glass microsphere resonant cavity filled with dye-doped nematic liquid crystal. We controlled the orientation of in-sphere liquid crystal and encapsulated it with polydimethylsiloxane film. The typical whispering gallery modes (WGMs) lasing spectra were obtained under a pulsed laser pump and the effects of the temperature and electric field on the peaks wavelengths were studied. The WGM spectra present a blueshift significantly with increasing temperature and electric field due to the decrease in the effective refractive index.